Asuhan Keperawatan Pada Pasien Dengan Cerebro Vaskuler Disease Stroke Iskemik Berdasarkan SDKI DAN SIKI di Rumah Sakit Wilayah Jakarta Selatan - Saudi, La (Indonesian Journal of Nursing Scientific, 2022)
Background: Ischemic stroke is a stroke that has clinical signs of dysfunction or damage to brain tissue caused by the accumulation of plaques so that there is a blockage of blood vessels which results in a lack of blood flow to the brain. Ischemic stroke causes damage to the brain which can result in impaired physical and sensory function, cognitive impairment, mild to severe motor impairment which is usually a clinical sign, namely hemiplegy or hemipration. More than 2.7 million people die from ischemic strokes each year. Stroke in Indonesia has a fairly large number of deaths in Asia, where the percentage of strokes in Jakarta is 11.44%. Destination: Where this research uses analatic descriptive research methods in the form of case studies to explore the problem of client nursing care. Method: By using a nursing care approach which includes assessment, nursing diagnosis, planning, implementation, and evaluation of nursing. It is known that the patient has headaches, high blood pressure, the presence of weakness in the right hand. Results: Nursing diagnoses in patients with ischemic stroke are the risk of ineffective cerebral perfusion, impaired physical mobility, risk of falling. The interventions used based on SIKI there are 9 actions applied in practice out of 17 actions based on theory where after being given nursing actions nursing problems the risk of cerebral perfusion is not effectively overcome, and 9 out of 10 nursing actions in impaired physical mobility after nursing actions nursing problems physical mobility disorders are partially resolved, as well as 11 nursing actions out of 12 nursing actions based on theory on risk falling after a nursing intervention the problem of falling risk is resolved. Evaluation: The results of the evaluation of the patient's headache decrease, blood pressure decreases, muscle strength increases, activity increases.